Improved glycaemic control and treatment satisfaction with a simple wearable 3‐day insulin delivery device among people with Type 2 diabetes. Issue 10 (5th July 2018) - Mader, J. K.; Lilly, L. C.; Aberer, F.; Poettler, T.; Johns, D.; Trautmann, M.; Warner, J. L.; Pieber, T. R.
Abstract: Aim: To evaluate the PAQ ® (CeQur SA, Horw, Switzerland), a wearable 3‐day insulin delivery device that provides set basal rates and bolus insulin on demand, in people with Type 2 diabetes. Method: Adults with Type 2 diabetes with HbA1c concentrations ≥53 and ≤97 mmol/mol (7.0 and 11.0%) while treated with ≥2 insulin injections/day were enrolled in two single‐arm studies comprising three periods: a baseline (insulin injections), a transition and a PAQ treatment period (12 weeks). Endpoints included HbA1c, seven‐point self‐monitored blood glucose, total daily dose of insulin and body weight. Safety was assessed according to examination, hypoglycaemic episodes and adverse device effects. Results: A total of 28 adults were enrolled (age 63 ± 7 years, 86% men, BMI 32.3 ± 4.3kg/m 2, Type 2 diabetes duration 17 ± 8 years, HbA1c 70 ± 12 mmol/mol (8.6 ± 1.1%), total daily insulin dose 58.7 ± 20.7 U), of whom 24 completed the studies. When transitioned to PAQ, 75% of participants continued on the first basal rate selected. After 12 weeks of PAQ wear, significant improvements from baseline were seen [HbA1c –16 ± 9 mmol/mol (95% CI –20, –12) or –1.5 ± 0.9% (95% CI –1.8, –1.1) P <0.0001], and at all seven self‐monitored blood glucose readings time points ( P ≤0.03). Total daily insulin dose increased by 12.1 ± 19.5 U (95% CI 3.9, 20.4; P =0.0058), the number of meal time boluses increased by 0.9 ± 1.5/day (95% CI 0.3, 1.5; P =0.0081) and body weight remained stable. Six participants had mild to moderate catheter site reactions and one mild skin irritation occurred. No participant experienced severe hypoglycaemia. Conclusions: Adults with Type 2 diabetes were safely transitioned from insulin injections to the PAQ and had significantly improved glycaemic control and treatment satisfaction with insulin therapy. (ClinicalTrials.gov identifiers: NCT02158078 & NCT02419859) What's new?: As Type 2 diabetes mellitus progresses, basal‐bolus insulin is required to achieve glycaemic targets; however, because of barriers associated with multiple daily injections (MDI), many people with Type 2 diabetes do not reach their goal. Randomized controlled trials evaluating continuous subcutaneous insulin infusion (CSII) via pumps vs MDI in people with Type 2 diabetes have shown that CSII achieves better glycaemic control and treatment satisfaction scores than MDI, but use is limited because of cost and complexity. The PAQ, a simple wearable CSII device provides freedom from daily injections. Results suggest the PAQ device achieves improved glycaemic control and treatment satisfaction scores among people with Type 2 diabetes. The PAQ device may be a viable alternative to MDI.